2014
DOI: 10.1302/0301-620x.96b4.33213
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement in HIV-positive patients

Abstract: We report the short-term follow-up, functional outcome and incidence of early and late infection after total hip replacement (THR) in a group of HIV-positive patients who do not suffer from haemophilia or have a history of intravenous drug use. A total of 29 patients underwent 43 THRs, with a mean follow-up of three years and six months (five months to eight years and two months). There were ten women and 19 men, with a mean age of 47 years and seven months (21 years to 59 years and five months). No early (< 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…23 Recent studies have shown more promising results of TJA in the nonhemophiliac, non-intravenous drug user, HIVþ population. [23][24][25][26][27][28][29][30][31] Boylan, et al 24 found that although HIVþ patients are at an increased risk for perioperative wound infections, they are not at an elevated risk for overall complications. Falakassa et al 23 hypothesized that one change contributing to improvement in complications is that the incidence of hemophilia with HIV infection has gone down due to improvements in blood screening and recombinant factor.…”
Section: Discussion Total Knee Arthroplasty In Hivþ Patientsmentioning
confidence: 99%
“…23 Recent studies have shown more promising results of TJA in the nonhemophiliac, non-intravenous drug user, HIVþ population. [23][24][25][26][27][28][29][30][31] Boylan, et al 24 found that although HIVþ patients are at an increased risk for perioperative wound infections, they are not at an elevated risk for overall complications. Falakassa et al 23 hypothesized that one change contributing to improvement in complications is that the incidence of hemophilia with HIV infection has gone down due to improvements in blood screening and recombinant factor.…”
Section: Discussion Total Knee Arthroplasty In Hivþ Patientsmentioning
confidence: 99%
“…[23,24] 3.11. HIV Graham et al (2014) reported of none correlation between having HIV and suffering from a periprosthetic joint infection. [25]…”
Section: Steroidsmentioning
confidence: 97%
“…Ainsi, dans une étude épidémiologique réalisée en Californie à partir de la base de données « The Nationwide Inpatient Sample » (NIS), il est noté que 61 % des patients VIH+ bénéficiant de cette prise en charge chirurgicale sont âgés de 22 à 50 ans versus 8 % dans la population VIH− dans cette même tranche d'âge (p < 0,01) [27]. Il n'a pas été démontré une augmentation significative des infections prothétiques postopératoires [28,29].…”
Section: Ostéonécrose Aseptiqueunclassified